Evaluation of oat accessions from different ecological groups in the steppe environments of Krasnodar Territory - N. P. Voytsutskaya; I. G. Loskutov; E. V. Blinova; L. Yu. Novikova (Труды по прикладной ботанике, генетике и селекции)
Background. Studying genetic diversity and identifying sources of valuable agronomic traits for specific environmental conditions is of great importance for plant breeders when they select source material for crop improvement. Materials and methods. Three hundred and seven oat accessions of various ecogeographic origin were tested under the conditions of the Kuban Experiment Station, a branch of the N.I. Vavilov All-Russian Institute of Plant Genetic Resources (VIR), in 2014–2019. Cv. ‘Valdin 765’ served as the reference. Weather conditions across the years of the study were contrasting in terms of the hydrothermal regime. Results. The inter-cultivar and year-to-year variability of the oat collection was analyzed in Krasnodar Territory and accessions promising for breeding were identified for a set of useful agronomic traits. The most significant differences among the studied oat accessions were recorded for the time of ripening and panicle characteristics. High yield of an accession under the conditions of Krasnodar Territory was associated with its high 1000 grain weight, which positively correlated with the duration of the period from panicle emergence to ripening and negatively with the length of the panicle, number of grains per panicle, plant height, and duration of the periods from germination to panicle emergence and from germination to ripening. Conclusion. The study of useful agronomic traits resulted in identifying oat accessions with the yield exceeding the reference (cv. ‘Valdin 765’) by 114–135%, that ripened 6–8 days earlier than the reference, were resistant to lodging, had short stems, manifested combined resistance (9 points) to crown and stem rust, low filminess (< 25%), good leafiness, high oil content (> 6%), increased protein content (> 14%), and high levels of yield structure components.